1988
DOI: 10.1080/02724936.1988.11748544
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal bacteraemia in Wesley Guild Hospital, Ilesa, Nigeria

Abstract: In a study on neonatal bacteraemia among the high-risk neonates admitted into our neonatal unit at Wesley Guild Hospital, Ilesha, the incidence of bacteraemia in babies born in the hospital was 17/1000 live births and 71.6/1000 total admissions into the unit. Gram-negative bacteria accounted for about 58.1% of bacteria isolated and Staphylococcus aureus for 62% of the isolated Gram-positive bacteria. Among the commonly used antibiotics, gentamicin is the most favoured by the sensitivity test. S. aureus appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 3 publications
5
17
1
Order By: Relevance
“…S. aureus was still the leading cause of Septicemia. This observation is in agreement with the work of some authors (Owa et al, 1988;Alausa et al, 1984;Olusanya et al, 1991;Ayliffe et al, 1977;Ako-Nai et al, 1999) but deviates from the reports from some hospitals from undeveloped countries by some authors. Gorbach and his colleagues (1992) reported that E. coli was the preponderant microbe.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…S. aureus was still the leading cause of Septicemia. This observation is in agreement with the work of some authors (Owa et al, 1988;Alausa et al, 1984;Olusanya et al, 1991;Ayliffe et al, 1977;Ako-Nai et al, 1999) but deviates from the reports from some hospitals from undeveloped countries by some authors. Gorbach and his colleagues (1992) reported that E. coli was the preponderant microbe.…”
Section: Discussionsupporting
confidence: 76%
“…This is contrary to the earlier reports by Owa et al (1988) at Wesley Guild Hospital, Ilesa, Alausa et al 1984 at Ibadan andDawodu et al (1980) but conforms with those of Antia-Obong et al (1990), Njokanma et al (1990), Olusanya et al (1991) Ako-Nai et al (1999 and Angyo et al (2001). Of the Gram-positive bacteria, the three common microbes were S. aureus, S. albus and Streptococcus faecalis among which Staphylococcus aureus had the highest occurrence while Klebsiella sp.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The reason for this is unknown. Suprapubic bladder aspiration for urine collection is preferred to a clean catch and mid-stream collection in neonates [34,53]. In addition, cultures of other body fluids like umbilical and eye discharge, joint effusion are routinely done while investigating septicaemia [12,29].…”
Section: Urine Culturementioning
confidence: 99%
“…Examination of the cerebrospinal fluid in neonatal septicaemia is mandatory since meningeal involvement occurs in about 30% of affected neonates, and the choice and the duration of antimicrobial therapy is modified in the presence of meningitis [14,34]. Cerebrospinal fluid cell count, Gram stain, protein and glucose concentration should be assessed in addition to culture as the results when taken together confirm or exclude meningitis [14].…”
Section: Cerebrospinal Fluid Culturementioning
confidence: 99%